A cohesive fracture model for predicting crack spacing and crack width in reinforced concrete structures. (September 2022) - De Maio, Umberto; Greco, Fabrizio; Leonetti, Lorenzo; Nevone Blasi, Paolo; Pranno, Andrea
Highlights: A cohesive approach to simulate crack propagation in RC specimens is used. An embedded truss model to capture concrete/rebar interaction is used. Crack width and crack spacing in RC structural elements are accurately predicted. Comparisons with experiments show the effectiveness of the proposed fracture model. Abstract: The cracking behavior analysis, in terms of crack spacing and crack width prediction, is essential to assess the damage and durability of a reinforced concrete (RC) structure. However, available numerical models cannot give satisfactory results in the cracking prediction due to the continuum representation of the concrete material often adopted in the numerical framework. Based on the cohesive finite element method, an interelement fracture model has been proposed here to investigate the cracking behavior, as well as its influence on the load-carrying capacity, of RC structural elements under static loading conditions. This fracture model is employed together with an embedded truss model for the rebars allowing them to be crossed by the cracks. Cracking analyses are performed on RC members subjected to tension and flexural loads. Comparisons with available experimental and numerical results have highlighted the effectiveness of the proposed model to investigate the cracking behavior in RC structures.